2015
DOI: 10.3109/09273972.2015.1107600
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Stereoacuity and 3-D Stereoscopic Entertainment

Abstract: Background/Aims: The perception of compelling depth is often reported in individuals where no clinically measurable stereoacuity is apparent. We aim to investigate the potential cause of this finding by varying the amount of stereopsis available to the subject, and assessing their perception of depth viewing 3-D video clips and a Nintendo 3DS. Methods: Monocular blur was used to vary interocular VA difference, consequently creating 4 levels of measurable binocular deficit from normal stereoacuity to suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Q ualitative work has demonstrated that many participants who are diagnosed as stereoblind when assessed using standard clinical tests report an enhanced perception of depth when viewing dynamic stereoscopic stimuli such as threedimensional (3D) films. [1][2][3] Although this demonstrates some residual ability to use information from the binocular comparison of retinal images, there are several differences between the characteristics of the stimuli involved. Several stereotests are commercially available for use in the clinic; however, they contain many artefacts preventing accurate threshold measurement of even static stereoacuity.…”
mentioning
confidence: 99%
“…Q ualitative work has demonstrated that many participants who are diagnosed as stereoblind when assessed using standard clinical tests report an enhanced perception of depth when viewing dynamic stereoscopic stimuli such as threedimensional (3D) films. [1][2][3] Although this demonstrates some residual ability to use information from the binocular comparison of retinal images, there are several differences between the characteristics of the stimuli involved. Several stereotests are commercially available for use in the clinic; however, they contain many artefacts preventing accurate threshold measurement of even static stereoacuity.…”
mentioning
confidence: 99%
“…Given the significant differences in presentation method and content, variability between clinical measures and 3‐D entertainment media is expected; however, the magnitude of that variation is surprising. To explore this discrepancy, we performed a series of tests to attempt to quantify this effect, which showed that in the presence of any measureable stereoacuity, subjects reported the impression of convincing depth when viewing the 3‐D videos . In a subgroup of seven non‐binocular subjects, no subject provided a clinically measurable level of disparity; however, responses to 3‐D entertainment media tasks ranged from nil to ‘appears very 3‐D’, and the depth order of five objects within a number of set scenes were correctly identified up to 55 per cent of the time (chance of getting it correct was > 20 per cent).…”
Section: Why Do People Without Measurable Stereo Report Seeing In 3‐d?mentioning
confidence: 99%
“…One challenge is the reduction from real life three-dimensional (3D) stereoscopic vision to virtual two-dimensional (2D) sight. 3D-vision is very important to perform any kind of manual tasks 5 . Therefore optimizing the visualization of the operative field is required especially in MIS.…”
Section: Introductionmentioning
confidence: 99%
“…As a disadvantage of the technique the surgeon must wear glasses and the equipment is expensive. Furthermore a relevant percentage of the population has deficits in binocular and stereoscopic vision, which could induce dizziness and nausea when using passive polarizing 3Dvideo technique 5 . This could deteriorate surgical performance at the end.…”
Section: Introductionmentioning
confidence: 99%